Conspiracy to commit crimes in illicit drug trafficking offense: Dogmatic analysis of second paragraph of the penal code article 296° - Rosas Castañeda, Juan Antonio (2019)
The article performs a dogmatic analysis of the fourth paragraph of article 296 of the criminal code, which regulates the crime of conspiracy to promote, favor or facilitate illicit trafficking of drugs and that, necessarily, reveal the existence of a common plan manifested among the participants in the crime, thus allowing to advance the punitive barriers of Criminal Law in order to protect important legal assets as well as for reasons of public order, for illicit drug trafficking and organized crime that it generates. Likewise, the article seeks to mention and develop the characteristics of this crime, the moment of consummation and accreditation at the jurisprudential level.